RAISING ANTIBODY AGAINST MOUSE SEX PHEROMONE BINDING PROTEIN IN RABBIT - S Kannan; M Krishnan; Tarvinder K Taneja; S Vinod Kumar (Tropical Life Sciences Research, 2007)
In the present investigation polyclonal antibody was raised against male sex pheromone binding protein (SPBP) of Mus musculus (L) (Swiss mice) and has been used to identify the pheromone binding proteins (PBPs) of mouse olfactory systems such as the main and accessory olfactory system with the liver and kidney tissue protein extracts were used as negative control. This maiden attempt authentically proves that the PBP is only present among the protein profiles of vomeronasal organ (VNO) and it was reported that this sex specific PBP is found not to be expressed in all other tissues including main olfactory system (MOS). Dalam kajian ini, antibodi poliklonal dihasilkan dengan protein pengikat feromon seks (sex pheromone binding protein, SPBP) daripada Mus musculus (L) (tikus jantan Swiss) dan digunakan untuk mengesan protein pengikat feromon (pheromone binding proteins, PBPs) dalam sistem olfaktori (deria) tikus seperti sistem deria bau utama dan aksesori dengan ekstrak protein tisu hati dan ginjal sebagai kawalan negatif. Usaha permulaan ini telah membuktikan bahawa PBP ialah protein tunggal yang hadir dalam kalangan profil protein organ vomeronasal (VNO). Didapati bahawa PBP yang jantina-spesifik ini tidak hadir dalam semua tisu lain termasuk sistem deria bau utama.